Isothiocyanate from Broccoli, Sulforaphane, and Its Properties - Vanduchova, Alena; Anzenbacher, Pavel; Anzenbacherova, Eva (Journal of medicinal food, 2019)
Sulforaphane is an isothiocyanate occurring in stored form as glucoraphanin in cruciferous vegetables such as cabbage, cauliflower, and kale, and at high levels in broccoli especially in broccoli sprouts. Glucoraphanin requires the plant enzyme myrosinase for converting it into sulforaphane. Sulforaphane is metabolized through mercapturic acid pathway, being conjugated with glutathione and undergoes further biotransformation, yielding metabolites. Sulforaphane is extensively investigated and is in the interest in medicine for its health benefits. It has been shown that sulforaphane may protect against various types of cancer, may also decrease the risk of cardiovascular disease, and help in autism and osteoporosis. Our review offers a short summary of interesting properties of sulforaphane. Both the in vitro and in vivo methods/models and clinical studies are mentioned.